2019
DOI: 10.1111/jdv.15455
|View full text |Cite
|
Sign up to set email alerts
|

The management and genetic background of pityriasis rubra pilaris: a single‐centre experience

Abstract: Background Pityriasis rubra pilaris (PRP) is a rare chronic inflammatory dermatosis with multifactorial aetiology. It is known that particular caspase recruitment domain family member 14 (CARD14) gene mutations are associated with familial PRP and certain forms of psoriasis. Additionally, few data are available about the role of CARD14 gene variants in sporadic PRP. The clinical picture is variable for the different types of PRP, therefore choosing the adequate treatment is often difficult, furthermore there a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The role of CARD14 in the pathogenesis of several inflammatory skin conditions was initially described through publications of familial cases of PsV and PRP (13)(14)(15). Gál et al (16) identified several CARD14 variants in almost half of their cases of PRP, but no correlation was found between the therapeutic response and the genetic background, which could have been due to a limited number of patients. To date, there are several reports that indicate that various CARD14 mutations may lead to autoinflammatory skin diseases such as plaque, pustular and/or erythrodermic types of psoriasis, pityriasis rubra pilaris, ichthyosis, and psoriatic arthritis (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…The role of CARD14 in the pathogenesis of several inflammatory skin conditions was initially described through publications of familial cases of PsV and PRP (13)(14)(15). Gál et al (16) identified several CARD14 variants in almost half of their cases of PRP, but no correlation was found between the therapeutic response and the genetic background, which could have been due to a limited number of patients. To date, there are several reports that indicate that various CARD14 mutations may lead to autoinflammatory skin diseases such as plaque, pustular and/or erythrodermic types of psoriasis, pityriasis rubra pilaris, ichthyosis, and psoriatic arthritis (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Both rs34367357 and rs2066964 were also associated with pustular psoriasis and psoriasis vulgaris in a Hans Chinese population [ 42 ]. These two nsSNPs were also reported to be associated with pityriasis rubra pilaris in a Hungarian population [ 43 ]. The association of nsSNPs rs34367357 and rs2066964 with disease severity, joint pain, and BMI was also determined.…”
Section: Discussionmentioning
confidence: 99%